IFAD Ethiopia country office will reinforce partnerships and increase effectiveness - Willebois, I. de (International Livestock Research Institute, 2011)
On 11 August 2011, the International Fund for Agricultural Development (IFAD) opened a country office on the ILRI campus in Addis Ababa. IFAD East and Southern Africa Regional Director Ides de Willebois explains that having IFAD staff 'in the field' based in country offices "makes all the difference" - helping us better understand country needs, and leading to better project design, better support and supervision, and ultimately better results. He also expects the physical location to reinforce partnerships for better impact.